Post-war and Post-Truth: The Masonic Affiliation of Margarita Nelken - Jardón Pardo de Santayana, Pelayo (2019)
After the Spanish Civil War, the representative Margarita Nelken (1893-1968) was tried by the Special Tribunal for the Repression of Freemasonry and Communism. She was accused of the crimes of Freemasonry and communism and judged by default. The only physical evidence her accusers had was a recommendation letter issued by the Barcelonese lodge Lealtad in 1924. However, the letter didn’t belong to her, but to a cabaret singer named Stella Margarita. Despite the lack of evidence, she was found guilty of having joined Freemasonry.